Pengaruh Metode Circuit Training terhadap Kebugaran Jasmani pada Klub Sepakbola - Andrian Fahmi; Muhammad Suhdy; Hengky Remora (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine whether there is an effect of circuit training on physical fitness at the football club Spartan Fc Lubuklinggau. The research method used in this study was quasi-experimental. The technique used in data collection in this study is a test technique in the Indonesian Physical Fitness (TKJI) test. The results showed an increase in the number of athletes who scored in the excellent category as many as 12 athletes, scores in the moderate category as many as six athletes. The highest score on the final test is 20, and the lowest score is 16. The average x value of the overall final test result based on the calculation is 18.11. The analysis results show that t count 14.28 is greater than t table 1.739 with a significant 5% (α = 0.05). In conclusion, there is a substantial effect after being given circuit training on physical fitness at the Spartan FC Lubuklinggau football club. Keywords: Circuit Training, Physical Fitness Test